1992
DOI: 10.1093/jn/122.12.2322
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Is Activated and Diacylglycerol Is Elevated in Epidermal Cells from Sencar Mice Fed High Fat Diets

Abstract: Studies reported here determined the effect of dietary fat level on membrane phospholipid composition, phosphoinositide labeling, 1,2-sn-diacylglycerol and protein kinase C activity in epidermal cells from female Sencar mice. Animals were fed either high fat (24.6 g/100 g diet) or control (5 g/100 g diet) diets at constant energy intake for 6 to 7 wk or 15 to 22 wk, and epidermal cells were isolated. The level of phosphatidylinositol was significantly lower in the animals fed the control diet than in the anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In a state of energy excess, intracellular long-chain fatty acyl-CoA (LC-CoA) and triglycerides accumulate (41). An accumulation of LC-CoA could also increase the concentration of diacylglycerol (DAG), an activator of protein kinase C (PKC) (44). Elevated malonyl-CoA inhibits carnitine palmitoyltransferase I, which is necessary for the transfer of fatty acids as LC-CoA through the mitochondrial membrane for oxidation and is thought to act as an intracellular signal of fuel availability.…”
Section: Mechanisms Involved In the Development Of Insulin Resistancementioning
confidence: 99%
“…In a state of energy excess, intracellular long-chain fatty acyl-CoA (LC-CoA) and triglycerides accumulate (41). An accumulation of LC-CoA could also increase the concentration of diacylglycerol (DAG), an activator of protein kinase C (PKC) (44). Elevated malonyl-CoA inhibits carnitine palmitoyltransferase I, which is necessary for the transfer of fatty acids as LC-CoA through the mitochondrial membrane for oxidation and is thought to act as an intracellular signal of fuel availability.…”
Section: Mechanisms Involved In the Development Of Insulin Resistancementioning
confidence: 99%
“…They proposed that bacteria expressing phospholipase C would be capable of such a conversion and that this was dependent upon the presence of secondary bile acids. Several studies have shown that a high-fat diet results in increased fecal concentrations of DAG (7,35,39). The interaction of DAG with PKC is thought to be stereospecific and stimulated only by DAG with a 1,2-sn configuration (33).…”
mentioning
confidence: 99%
“…In Sencar mice fed 24.5% corn oil diets for six to seven weeks, PKC activity was elevated compared with a 5% corn oil diet in the particulate fraction from mice fed the high corn oil diet (17). However, in studies in which Sencar mice were prefed for 13 weeks agar-containing control and highfat diets with energy from fat and carbohydrate balanced, particulate PKC activity was lower in mice fed the high-fat diet than in control mice (18).…”
Section: Introductionmentioning
confidence: 93%